Enabling dynamic ultralong organic phosphorescence in molecular crystals through the synergy between intramolecular and intermolecular interactions. Issue 22 (5th May 2020) - Yang, Zhan; Ubba, Eethamukkala; Huang, Qiuyi; Mao, Zhu; Li, Wenlang; Chen, Junru; Zhao, Juan; Zhang, Yi; Chi, Zhenguo
Abstract : Dynamic ultralong organic phosphorescence in molecular crystals is enabled through the synergy between intramolecular and intermolecular interactions. Abstract : Ultralong organic phosphorescence (UOP) materials exhibiting persistent emission features can be used for applications such as information encryptions, bioimaging, and display. Until now, the molecular design of UOP materials has been mainly focused on intermolecular interactions without consideration of intramolecular interactions. Here, a series of highly twisted molecules exhibit non-radiative decay as low as 1.01 s −1 due to the restriction of the excited molecular motions through the synergy between intramolecular and intermolecular interactions in the molecular crystals. A unique insight regarding the importance of intramolecular interactions in suppressing non-radiative decay as well as the intermolecular interactions is provided in this contribution. Significantly, two of the phosphors display color-dynamic UOP emissions in a wide range (from pink to white then orange), which exhibit linearly tunable emissions after ceasing the excitation source. Moreover, due to the dual ultralong emission feature, a stable white-light persistent emission is realized for the first time in the molecular crystal. These findings provide the opportunity for the development of dynamic luminescence in organic materials.